Investigation on non-contact ultrasonic-assisted laser directed energy deposition of 316 austenitic stainless steel - Qinghua Zhang; Yibo Liu; Yongqing Zhao; Jiawei Guo; Haoyu Kong; Huisheng Ren; Qi Sun; Qingjie Sun (Journal of Materials Research and Technology)
This study utilized non-contact ultrasound-assisted laser directed energy deposition (LDED) technology for in-situ repair of 316L austenitic stainless steel. It investigated the influence mechanism of non-contact ultrasonic on the dynamic behavior of plasma and melt pool during the deposition process, as well as the influence of ultrasound induced vibration and thermal cycling changes on the microstructure and mechanical properties. The results indicated that ultrasound could be transmitted into the molten pool through non-contact means, causing severe vibration of the liquid metal, which promoted the spreading and wetting of the liquid metal to both sides and facilitated the escape of internal pores in the molten pool. Simultaneously, ultrasound suppressed the plasma height, enhanced its heat exchange effect with the molten pool, and together with the thermal effect of ultrasound, reduced the cooling rate of the molten pool. After applying ultrasound, the surface smoothness of the deposition layer was improved, and the cavitation effect of ultrasound effectively refined the grain size, reducing it from 68.8 μm to 48.9 μm. The maximum orientation density of grains also decreased from 9.384 to 7.505. The reduction in cooling rate prolonged the transformation time from ferrite to austenite, decreasing the ferrite content in the deposition layer and altering the ferrite structure from lath to skeleton. Meanwhile, the slowed cooling rate promoted the merging of LAGBs and the growth of HAGBs, reducing the dislocation density of the sedimentary layer. Based on the above reasons, the tensile and corrosion resistance of the cladding layer have been enhanced.